EVALUASI KETERAMPILAN MENULIS BAHASA ARAB (MAHARAH KITABAH) BERDASARKAN KURIKULUM MERDEKA BELAJAR - Sufiyani Nur Mawaddah; Isnaini Khoirotun Ni’mah; Anis Zunaidah (Nahdlatul Lughah, 2023)
Today, learning to write is mostly presented in the form of theory, not much practice of writing. Writing skills that are not matched by practice are one of the factors that make students less skilled at writing. Writing skill (maharah al-kitabah) is the highest skill of the four language skills. Moreover, writing in Arabic must pay attention to aspects of al-qawaid (nahu and sharf), imla' and khat. The presence of the Independent Learning curriculum is a breath of fresh air for the world of education. Among the focuses of the Independent Learning curriculum innovation is on the evaluation aspect of learning. Writing this article aims to find out the evaluation of learning Arabic writing skills (maharah kitabah) in the Independent Learning Curriculum. The method used in this research is library research. The results of this study indicate that the assessments in Independent Learning are more directed at continuous assessments such as observation, performance, projects, written tests, oral tests, assignments, and portfolios (group assignments, written work, practicum, and so on). This kind of assessment is called an authentic assessment and is very relevant to be applied to learning writing skills (maharah kitabah).